2011
DOI: 10.3892/ol.2011.452
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical diagnosis of synchronous multiple primary lung cancer

Abstract: Abstract. The diagnosis of synchronous multiple primary lung cancer (SMPLC) remains a formidable challenge. The aim of the present study was to identify useful clues for the clinical diagnosis of SMPLC, in particular for the early stages. The medical records of 10 patients diagnosed with SMPLC with different histological types were analyzed retrospectively. Chest computed tomography (CT) findings showed two pulmonary lesions in all patients. The two lesions displayed malignant characteristics of primary lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…It is worth noting that the patient's smoking habit confirms the results of previous reports [10] suggesting that tobacco smokers are more susceptible to synchronous lung cancers.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It is worth noting that the patient's smoking habit confirms the results of previous reports [10] suggesting that tobacco smokers are more susceptible to synchronous lung cancers.…”
Section: Discussionsupporting
confidence: 78%
“…Selected studies are presented in Tables I and II. As mentioned above, SMPLCs are diagnosed relatively rarely. The analyses by individual authors presented in Table I [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] were based on sets of 3 [19] to 175 [17] case studies gathered over periods of time lasting from 4 [26] to 28 [28] years. The included authors conducted retrospective observations and confronted the employed treatment with the achieved long-term survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUC16 was identified as the most overexpressed antigen in ovarian cancer (6,7). Since its identification, MUC16 has been shown to be overexpressed in several other cancers, including breast (21), pancreatic (20,101), non-small-cell lung cancer (102,103), intrahepatic cholangiocarcinoma-mass forming type (104), adenocarcinoma of the uterine cervix (105), and adenocarcinoma of the gastric tract (106,107) (Table 2). Not much is known with respect to the specific role of MUC16 in cancer except for ovarian, pancreatic, and breast cancer, which has been discussed below.…”
Section: Malignant Diseasementioning
confidence: 99%
“…Our study of the use of computed tomography (CT) images showed that diagnosis of synchronous MPLC might be delayed or mistaken for intrapulmonary metastasis, and that the malignant characteristics of primary lung cancer lesions may provide valuable diagnostic clues. 19 Although the introduction of more sensitive CT or positron emission tomography scanning and fluorescence endoscopy (together with increased surveillance) have improved the detection of MPLC, 15,[20][21][22][23] there remains a lack of uniform guidelines for MPLC diagnosis.…”
Section: Introductionmentioning
confidence: 99%